PENYIRAMAN TANAMAN OTOMATIS MENGGUNAKAN CAPACITIVE SOIL MOISTURE SENSOSOR V2.O BERBASIS ARDUINO UNO - muhamad sahrul; Endang; Yuliarman Saragih (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2022)
So far, watering plants is done manually. However, sometimes humans do not have enough time to water plants and do not know how much water is needed by plants. Therefore, an automatic plant watering system was created to maintain plant quality, save time and save energy. This tool is made because everyone is not necessarily able to water plants properly and correctly, because it takes knowledge of the procedures for watering the plants themselves so they don't die easily and grow fast. This research was conducted by designing a structure that can water plants automatically using a capacitive soil moisture sensor v2.0 humidity sensor which is controlled by Arduino Uno and displayed through a 16x2 I2c display according to soil moisture and pH. The plant sprinkler system that has been made can water the plants automatically. The display screen will display the value of the soil condition whether dry, moist or wet according to the readings from the soil moisture sensor. Keywords: Arduino Uno; capacitive soil moisture sensor v2.0; Humidity Sensor; Soil pH.